Pharmacokinetic–Pharmacodynamic Modeling of Enrofloxacin Against Escherichia coli in Broilers - Sang, KaNa; Hao, HaiHong; Huang, LingLi; Wang, Xu; Yuan, ZongHui (Frontiers in Veterinary Science, 2016)
The purpose of the present study was to establish a pharmacokinetic/pharmacodynamic (PK/PD) modeling approach for the dosage schedule design and decreasing the emergence of drug-resistant bacteria. The minimal inhibitory concentration (MIC) of 929 E. coli isolates from broilers to enrofloxacin and ciprofloxacin were determined following CLSI guidance. The MIC50 was calculated as the populational PD parameter for enrofloxacin against E. coli in broilers. The 101 E. coli strains with MIC closest to the MIC50 (0.05µg/mL) were submitted for serotype identification. The 13 E. coli strains with O and K serotype were further utilitzed for determining pathogencity in mice. Of all the strains tested, the E. coli designated strain Anhui 112 was selected for establishing the disease model and PK/PD study. The pharmacokinetics (PKs) of enrofloxacin after oral administration at the dose of 10mg/kg body weights (BW) in healthy and infected broilers was evaluated with high-performance liquid chromatography (HPLC) method. For intestinal contents after oral administration, the peak concentration (Cmax), the time when the maximum concentration reached (Tmax), and the area under the concentration-time curve (AUC) were 21.69~31.69μg/mL, 1.13~1.23h, and 228.97~444.86μg.hr/mL, respectively. The MIC and minimal bactericidal concentration (MBC) of enrofloxacin against E. coli (Anhui 112) in Mueller-Hinton (MH) broth and intestinal contents were determined to be similar, 0.25μg/mL and 0.5μg/mL respectively. In this study, the sum of concentrations of enrofloxacin and its metabolite (ciprofloxacin) was used for the PK/PD integration and modeling. The ex vivo growth inhibition data were fitted to the sigmoid Emax (Hill) equation to provide values for intestinal contents of 24h area under concentration–time curve/MIC ratios (AUC0~24h/MIC) producing, bacteriostasis (624.94h), bactericidal activity (1065.93h) and bacterial eradication (1343.81h). PK/PD modeling was established to simulate the efficacy of enrofloxacin for different dosage regimens. By model validation, the protection rate was 83.3%, demonstrating that the dosage regimen of 11.9mg/kg BW every 24h during 3 days provided great therapeutic significance. In summary, the purpose of the present study was to first design a dosage regimen for the treatment E. coli in broilers by enrofloxacin using PK/PD integrate model and confirm that this dosage regimen presents less risk for emergence of floroquinolone.